The Influence of Operation Conditions of Gedi Leaf Drying Process (Abelmoschus Manihot. L) On Antioxidant Activity - Siska Ayu Anggraini; Tri Yuni Hendrawati; Ismiyati Ismiyati (Journal of Applied Sciences and Advanced Technology, 2020)
Gedi leaf (Abelmoschus manihot L) is a type of plant that is categorized in a group of medicinal plants / herbal plants and grows mostly in North Sulawesi and is a tropical plant of the Malvacea family, gedi leaves contain flavonoids, tannins, alkaloids, anthraquinone saponins and anthocyanins which have antioxidant activity. Antioxidants are important compounds in maintaining a healthy body. Because it functions as a free radical scavenger. In this study, examined the use of gedi leaf drying as an alternative source of antioxidants to be applied for face masks. Gedi leaf powder sample was tested by Proximate testing to determine the characteristics of gedi leaf powder and gedi leaf powder used as a powder mask preparation. The method used to obtain dry gedi leaves is the oven with a temperature variation used 40; 50; 60 ° C and 5 time variations; 6; 7 hours. The results showed that the best yield of drying gedi leaf powder against time to temperature was 5 hours with a temperature of 70⸰C, from the best yield it was processed into masks divided into 3 formulas, namely 10; 20; 30% dried gedi leaves in a 40gr formula with rice flour as an added ingredient. From the results of making 3 dry gedi leaf mask formulas tested proximate with the help of 20 panelists, the results of the panelists' assessment of formula 2 with 20% gedi leaves are preferred and get a value of 20% higher. Measurement of the 3 formulas obtained pH values of gedi leaf masks of 5.63, 5.68, and 5.72.